The Paradigm of Migranomics - Gaidutskiy, Andriy (Information & Media, 2020)
The article analyses the influence of international labor migration on the development of the host and home economies. The purpose of the article is to show that thanks to migration the host countries could improve their development and their home countries could receive enough remittance flows to stabilize economic situation and continue reforms. And in the home countries migrants’ remittances use both for consumer and investment purposes. Based on an integrated approach to the study of these problems, the paradigm of migranomics has been formulated for the first time. At the same time, migranomics should be understood as a special part of the world economy, which is developed due to the effective use of labor of migrants in their countries of employment and the means of remittances of migrants for consumer and investment purposes in their homeland. The experience of the development of migration in the US, Canada, Poland and other EU countries is revealed through the use of immigrant labor. The conclusion shows that the achievements and perspectives of the development of migranomics in developing countries, including in Ukraine, and it is based on economic implications of migration remittances.